INFLUENCE OF PERSONAL QUALIFICATIONS, THE ENVIRONMENT AND INSTITUTIONAL ENVIRONMENT MONITORING PROCESS IN THE PROVISION OF LOAN / FINANCE EMERGING OF NPL / NPF (Comparative Studies on Conventional Banks and Islamic Banking in Indonesia) - Hendy Herijanto (Business and Entrepreneurial Review, 2011)
This study begins to approach the issue by applying the agency theory, moral hazards theory, and stakeholder theory, as well as the “Adverse Selection” theory by Stiglitz and weiss (1981) and “Bad Management” by Berger and Young (1997). The last two theories mainly refer to the processing part of the matter to start with, but the last one uses a concept where it is the management (of abank) that must be questioned how efficient they do their job. Management is a wide concept, and such as, which managerial factors that could affect the creation of NPL/NPF must be detailed. This study could be breakdown the three group attributes above to constitute eleven factors, i.e. credit knowledge and skills, integrity and professionalism, spirituality level, moral leadership, corporate culture, hard budget policy, reward and penalty system, credit culture, reputation checking, due diligence and care, and supervision or audit. Further this study hypothesizes that these eleven factors could affect the creation of NPL/NPF, and the creation of NPF is lower inIslamic bank than that of NPL in conventional bank, because the application of those factors is hypothesized stronger or better in the first type of bank by its management than in the second, due to its philosophy and the laws that govern. A research has been completed, employing statistical variance and F test on the data gathered from all the 28 islamics bank/banking units in existence, and 28 conventional banks. The study has concluded that all the eleven factors of the internal management can influence the creation of NPL/NPF in both banks. The study further proves that these factors, independently or as the combination of all, are applied better in Islamic bank than in conventional bank, due to the fact that the syariah concept itself not only applied in conducting the business, but also used as a moral reference in dayly working environment. As a result, theaverage level of NPF is lower in bank syariah than NPL level of conventional bank under study.